Secure Group Communication in WSN based on Integrated approach of Chaos and Neural Network - S Annapurna, H; Siddappa, M (International Journal of Engineering and Technology, 2018)
With advancement in technology,Â Â at present, there is possibility to develop low cost sensors in the area of wireless sensor network. Often in practice, there are huge numbers of sensors, which are deployed in hostile environment. Hence, there is a need to develop the security mechanism so that defined applications can serve the purpose. Two areas come under security consideration, protection for communication data and authentication of communicating parties. In this paper, chaos and neural network based centralized security mechanism has been developed. Two different types of chaotic maps, Lozi and Logistic maps have been integrated with feed-forward architecture of neural network to deliver the security provision. The sensitiveness with initial conditions of chaos has been exploited for key development. Proposed method not only provides high level of security but also carries high level of flexibility, scalability and computational efficiency.Â Â